Bioactivity of aqueous extract of Jacaranda spp. (Bignoniaceae) on Plutella xylostella L. 1758 (Lepidoptera: Plutellidae) - Santos,Leticia Paula dos (2022)
Abstract The high consumption rate of vegetables stimulates the cultivation and increases the demand regarding the adequacy of the production processes. The attack of the pest Plutella xylostella causes high losses by reducing product quality, typifying a phytosanitary problem. This study aimed to verify the bioactivity of aqueous extracts of leaves of Jacaranda decurrens and Jacaranda mimosifolia at concentrations of 5, 10, and 15% on the insect. The choice test was carried out at the laboratory to determine the food effect of plant extracts and evaluate changes in the life cycle of insects exposed to active compounds through the analysis of biological parameters. Plant extracts of J. decurrens and J. mimosifolia presented with phagodeterrent classification in the choice experiments. The three J. decurrens extract concentrations promoted a prolongation of larval and pupal duration, while the duration of individuals treated with J. mimosifolia at 10% was significantly reduced. Occurred reduction in larval survival of individuals treated with aqueous extracts of J. decurrens and J. mimosifolia. Eggs from treatments with aqueous extract of J. decurrens and J. mimosifolia had reduced survival. Pupal survival of individuals treated with extract at 15% showed a significant reduction compared to the treatments at 5% and 10%. Pupae from the treatment with aqueous extract of Jacaranda mimosifolia showed a reduction in biomass in the treatment at 15% differing from the control e 5%. Thus, the aqueous extracts of the species J. decurrens and J. mimosifolia show insecticidal potential in the tests performed on P. xylostella.